S112 The natural history of wheeze from birth to adult life: a cohort study. (16th November 2010) - Burr, M L; Dunstan, F D J; Hand, S; Jones, K P; Rolf, S
Abstract : Introduction and objectives: Wheeze is a common symptom at all ages. Its natural history from birth to adulthood was studied in a birth cohort of individuals at high risk of atopic illness. The objective was to ascertain factors associated with wheeze at different ages, distinguishing between wheeze that occurred at successive time points (persistent wheeze) and wheeze newly occurring (incident wheeze). Methods: 497 infants were selected antenatally as having a first-degree relative with a history of asthma, hay fever or eczema. During their first year and at 7 years the children were examined, symptoms were recorded, skin prick tests performed and serum IgE measured. At 15 and 23 years further questionnaires were completed and (at 23) blood and skin tests performed. Results: Information was obtained on 483 individuals at 1 year, 453 at seven, 363 at 15 and 304 at 23. The prevalence of wheeze was fairly constant over time (around 30%), remission being balanced by incidence over each interval. Wheeze at 1 year predicted wheeze at ages seven and 15, and at seven it predicted wheeze at 15 and 23, but it was associated with different factors at different times and according to whether it was persistent or incident. In infancy it was related to non-atopic factors such as infection, maternal smoking and breastfeeding (protective). Persistent wheeze to age 15 was related to respiratory infections in infancy and to atopy. Incident wheeze from one to 7 years was strongly associated with atopy, while late-onset wheeze was related to rhino conjunctivitis, smoking and (marginally) body mass. Conclusions: Advances in the understanding and prevention of wheeze may be assisted by directing attention to maternal smoking, breastfeeding and respiratory infections in infancy, atopy in childhood, rhino conjunctivitis in adolescence, and smoking and perhaps obesity in adult life.